ЛИНГВИСТИК ВОСИТАЛАР ОРҚАЛИ ШАХС ХУСУСИЯТЛАРИНИНГ НАМОЁН БЎЛИШИГА ДОИР (Scientific journal of the Fergana State University, 2023)
Language and its social functions is considered in this article. Appearance of personal abilities are presented through examples of phonetic, morphemic, lexic and syntactic means taken from prose language.